10.1111/acn.v9999.9999 (CrossRef Listing of Deleted DOIs, 2000)
The use of Patient-Reported Outcome Measures (PROMs) and Patient-Reported Experience Measures (PREMs) in cardiovascular disease (CVD) healthcare is an area of global growing interest for improving patient clinical outcomes. Historically, PROMs and PREMs have evolved over the last three decades through the development of standardized measurement sets and integration with digital and Artificial Intelligence (AI) systems to support benchmarking and quality improvements in health servicing. As the global prevalence of CVD continues to rise, compounded by population aging and the shift toward community-based care, PROMs and PREMs have gained increasing recognition. However, despite growing evidence and policy endorsements, the strategic use of PROMs and PREMs in routine CVD healthcare remains fragmented and underutilized. This Discussion paper examines global developments, identifies persistent implementation gaps, and proposes future directions for integrating PROMs and PREMs into AI-driven and digitally-enabled, value-based CVD healthcare.